GROUP INVESTIGATION (GI) TO INCREASE STUDENT MATHEMATICS LEARNING OUTCOMES - Nisa, Titin Faridatun; Cuevas, Jonas Villegas (Transpublika Publisher, 2022)
This study aims to determine the increase in student learning outcomes at MTsN 3 Malang after the group investigation type cooperative learning model was applied. This study is a quantitative approach study. The population in this study were all students of class VII in MTsN 3 Malang as many as five classes, but as samples taken two classes, namely class VII/B as many as 20 students as the control class and class VII/E as many as 20 students as the experimental class. Meanwhile, data collection on the ability of students' mathematics learning outcomes using an instrument in the form of a test. The data processing used one-party t-test statistics. The findings reveal that by applying the group investigation (GI) type cooperative learning model, it can improve the mathematics learning outcomes of MTsN 3 Malang students, rather than the mathematics learning outcomes of students who are taught using the STAD learning model.